2006
DOI: 10.1107/s1600536806017983
|View full text |Cite
|
Sign up to set email alerts
|

3-(3-Bromophenyl)-1-(4-bromophenyl)prop-2-en-1-one

Abstract: In the title compound, C15H10Br2O, the dihedral angle between the benzene rings is 48.0 (1)°. The crystal structure is stabilized by weak inter­molecular Br⋯Br contacts and C—H⋯π inter­actions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…A survey of the Cambridge Structural Database (CSD; Groom et al, 2016) showed that existing similar structures include (2E)-1-(4-bromophenyl)-3-(4-fluorophenyl)prop-2-en-1-one (refcode NURCIN; Dutkiewicz et al, 2010), 1-(4-bromophenyl)-3-(4-chlorophenyl)prop-2-en-1-one (LEPYIP; Yang et al, 2006), 1,3-bis(4-bromophenyl)prop-2-en-1-one (LEHROG; Ng et al, 2006), (E)-1-(4-bromophenyl)-3-(4iodophenyl)prop-2-en-1-one (IWALAV; Zainuri et al, 2017) and 3-(3-bromophenyl)-1-(4-bromophenyl)prop-2-en-1-one (ODEDEH; Teh et al, 2006). Four compounds (NURCIN, LEPYIP, LEHROG and IWALAV) contain only parasubstituted rings.…”
Section: Database Surveymentioning
confidence: 99%
“…A survey of the Cambridge Structural Database (CSD; Groom et al, 2016) showed that existing similar structures include (2E)-1-(4-bromophenyl)-3-(4-fluorophenyl)prop-2-en-1-one (refcode NURCIN; Dutkiewicz et al, 2010), 1-(4-bromophenyl)-3-(4-chlorophenyl)prop-2-en-1-one (LEPYIP; Yang et al, 2006), 1,3-bis(4-bromophenyl)prop-2-en-1-one (LEHROG; Ng et al, 2006), (E)-1-(4-bromophenyl)-3-(4iodophenyl)prop-2-en-1-one (IWALAV; Zainuri et al, 2017) and 3-(3-bromophenyl)-1-(4-bromophenyl)prop-2-en-1-one (ODEDEH; Teh et al, 2006). Four compounds (NURCIN, LEPYIP, LEHROG and IWALAV) contain only parasubstituted rings.…”
Section: Database Surveymentioning
confidence: 99%
“…A search of the Cambridge Structural Database (Version 5.39, last update November 2017; Groom et al, 2016) revealed one closely related compound that differs in the halogen substitution attached to the aldehyde ring, namely 3-(3-bromophenyl)-1-(4-bromophenyl)-prop-2-en-1-one (Teh et al, 2006). Other related compounds, which differ in the halogen substitution at the para-position of the aldehyde ring include (2E)-1-(4-bromophenyl)-3-(4-fluorophenyl)prop-2-en-1-one (Dutkiewicz et al, 2010), 1-(4-bromophenyl)-3-(4-chlorophenyl)prop-2-en-1-one (Yang et al, 2006), 1,3-bis(4-bromophenyl)prop-2-en-1-one (Ng et al, 2006), (E)-1-(4-bromophenyl)-3-(4-iodoophenyl)prop-2-en-1-one (Zainuri et al, 2017) and (E)-3-(4-bromophenyl)-1-(4-fluorophenyl)prop-2-en-1-one (Zaini et al, 2018).…”
Section: Database Surveymentioning
confidence: 99%
“…Molecules that possess such a system have relatively low redox potentials and have a greater probability of undergoing electron-transfer reactions. Crystal structures have been reported for 3-(3-bromophenyl)-1-(4-bromophenyl)prop-2-en-1-one (Teh et al, 2006), 3-(3bromophenyl)-1-(2-naphthyl)prop-2-en-1-one (Moorthi et al, 2007), (E)-1-(3-bromophenyl)-3-(4-ethoxyphenyl)prop-2-en-1-one (Fun et al, 2008), (E)-3-(biphenyl-4-yl)-1-(3-bromophenyl)prop-2-en-1-one (Dutkiewicz et al, 2009), (2E)-1-(3-bromophenyl)-3-(6-methoxy-2-naphthyl)prop-2-en-1-one (Harrison et al, 2010), (2E)-1-(3-bromophenyl)-3-(4,5dimethoxy-2-nitrophenyl)prop-2-en-1-one (Jasinski et al, 2010), (E)-1-(3-bromophenyl)-3-(3,4-dimethoxyphenyl)prop-2-en-1-one (Escobar et al, 2012), (E)-1-(3-bromophenyl)-3-(4nitrophenyl)prop-2-en-1-one (Harini et al, 2017) and (E)-1-(3-bromophenyl)-3-(3-fluorophenyl)prop-2-en-1-one (Rajendraprasad et al, 2017). We herewith report the crystal and molecular structure of the title compound.…”
Section: Chemical Contextmentioning
confidence: 99%